Paideia Patristic Education: Analysis into the acquisition of soft skills in Universities in Machakos County, Kenya - Njogu Wachira, Ann; Mutai, Noah Cheruiyot; Bensam Sambiri, Benjamin (GILE Journal of Skills Development, 2024)
The acquisition of soft skills is increasingly recognized as a crucial component of higher education, essential for preparing students to meet the challenges of the modern workforce. This study investigates the process of acquiring soft skills through Paideia Patristic Education (PPE) in universities in Machakos County, Kenya. This quantitative study aims to evaluate the effectiveness of the PPE framework in promoting key soft skills such as communication, teamwork, critical thinking, and flexibility. Purposive sampling technique was used to target specific faculty members and students. Data was collected using structured and semi-structured questionnaires. The study's results show that PPE has a positive effect on students' soft skills, particularly in enhancing their ability to work effectively in teams and collaborate. Universities in Machakos County and beyond should strongly consider incorporating Paideia Patristic Education principles into their curricula. This would help cultivate crucial soft skills in students, better equipping them for the challenges of the contemporary job market.